Phineas Finn : The Irish Member - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2006)
"Phineas Finn" by Anthony Trollope is a novel first published serially from 1867 to 1868. It follows a charming young Irishman who enters British Parliament with no salary and little fortune. To survive in London's political world, Phineas must navigate party politics, contentious reforms, and his romantic entanglements with several women of wealth. His friendships, ambitions, and heart pull him between loyalty and opportunity, forcing difficult choices that will determine both his political career and personal future. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Phineas_Finn
Release date is 2006-04-07
E-text prepared by Joseph E. Loewenstein, M.D.
Keywords: London (England) -- Fiction; Political fiction; Legislators -- Fiction; Palliser, Plantagenet (Fictitious character) -- Fiction; Dublin (Ireland) -- Fiction